2018
DOI: 10.1101/368357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR/Cas9 gene editing for the creation of an MGAT1 deficient CHO cell line to control HIV-1 vaccine glycosylation

Abstract: Over the last decade multiple broadly neutralizing monoclonal antibodies (bN-mAbs) to the HIV-1 envelope protein, gp120, have been described. Surprisingly many of these recognize epitopes consisting of both amino acid and glycan residues. Moreover, the glycans required for binding of these bN-mAbs are early intermediates in the N-linked glycosylation pathway. This type of glycosylation substantially alters the mass and net charge of HIV envelope (Env) proteins compared to molecules with the same amino acid seq… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 81 publications
6
24
1
Order By: Relevance
“…With PELC/CpG combination adjuvant, a 0.2 mg dose of CHO-rH7 but not CHO-rH7 (KIF) and CHO-rH7 (KIF + E) elicited a protective response and conferred protection in survival and body weight recovery of the immunized mice following live virus challenges. The results are in contradictory to HIV-1 gp120 antigen produced in CHO cells where limiting N-linked glycosylation to early oligomannose glycans can enhance the HIV-1 subunit vaccine efficacy [42]. Our present results demonstrated that CHO cell-expressed rH7 antigens containing terminally sialylated complex type N-glycans, but not high mannose-type or single GlcNAc-type N-glycans, can provide protection against H7N9 infections.…”
Section: Discussioncontrasting
confidence: 72%
“…With PELC/CpG combination adjuvant, a 0.2 mg dose of CHO-rH7 but not CHO-rH7 (KIF) and CHO-rH7 (KIF + E) elicited a protective response and conferred protection in survival and body weight recovery of the immunized mice following live virus challenges. The results are in contradictory to HIV-1 gp120 antigen produced in CHO cells where limiting N-linked glycosylation to early oligomannose glycans can enhance the HIV-1 subunit vaccine efficacy [42]. Our present results demonstrated that CHO cell-expressed rH7 antigens containing terminally sialylated complex type N-glycans, but not high mannose-type or single GlcNAc-type N-glycans, can provide protection against H7N9 infections.…”
Section: Discussioncontrasting
confidence: 72%
“…6A) between the binding affinity of rgp120 A224-N332 produced in MGAT1 - CHO cells as measured by EC50 (1.33 nM) for PG9, when compared to the RV144 antigen, rgp120 A224, produced in CHO S cells (no binding plateau). This result is in concordance with data from previous transient transfection studies (57, 58). Binding of bN-mAbs to protein produced in the 5F MGAT1 - CHO cell line was indistinguishable to protein produced by transient transfection in MGAT1 - CHO cells.…”
Section: Resultssupporting
confidence: 93%
“…6F). This difference was also previously reported (57). VRC01 is an anti-CD4 binding site antibody with low affinity for glycan in glycan-array assay (65).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…ERV‐edited clones were found to proliferate at comparable rates as polyclonal populations, empty vector‐treated and untreated cell controls, with a density reaching approximately 12.5×10 6 cells/ml after 5 days in culture (Figure S8A). Such a cell density concords with the expected CHO‐K1 doubling time of roughly 20 hr (Byrne et al, ). However, two Myr2‐edited clones (C02, D12) and one PPYP6‐mutated clone (K14) showed slightly modified cell cycle durations, and the maximal viable cell density of C02 was reduced, although this effect was not statistically significant.…”
Section: Resultssupporting
confidence: 64%